A suspicious skin nodule with dilated chest veins: the importance of a full skin examination. (1st September 2022) - Sheppeard, Rhian; Mitchell, Charles; Woo, Wen‐ai; Simmonds, Roshni
Abstract: This letter outlines the case of a new‐onset skin nodule, which led to the diagnosis of both a primary bronchial carcinoma and a cutaneous metastatic squamous cell carcinoma deposit. This case highlights the importance of a full skin examination to pick up important clinical signs as, although these can be subtle, they can have a significant effect on further management.